2015
DOI: 10.1007/s12134-015-0436-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Employment-Related Migration Reduce Poverty in India?

Abstract: Using the unit data from the 64th round of the National Sample Surveys, 2007-08 on employment, unemployment, and migration, covering 125,578 households, this paper estimates the level, depth, and severity of poverty among nonmigrants and intra-state migrants, inter-state migrants, and emigrants in India. Based on the out-migration of any members of the household for employment at place of origin and using place of last residence definition, households are classified into intrastate migrants, inter-state migran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Many studies have shown that labor migration positively affects the well-being of displaced households (Fukase, 2013;Ngoma & Ismail, 2013;Sikder & Ballis, 2013;Zeitlyn et al, 2014). Similarly, Mohanty, Mohapatra et al (2015) who demonstrated that the level, depth, and severity of poverty among migrant households was lower than those among non-migrant households. Migrants who migrated out had higher income per capital and better education in comparison with non-migrants (Vakulabharanam & Thakurata, 2014).…”
Section: Introduce the Problemmentioning
confidence: 96%
“…Many studies have shown that labor migration positively affects the well-being of displaced households (Fukase, 2013;Ngoma & Ismail, 2013;Sikder & Ballis, 2013;Zeitlyn et al, 2014). Similarly, Mohanty, Mohapatra et al (2015) who demonstrated that the level, depth, and severity of poverty among migrant households was lower than those among non-migrant households. Migrants who migrated out had higher income per capital and better education in comparison with non-migrants (Vakulabharanam & Thakurata, 2014).…”
Section: Introduce the Problemmentioning
confidence: 96%
“…Most of the destination states regard the migrants as vagrants and perceive migration as a threat to their stability and social order. The access to PDS (Public Distribution System), health care, housing, immunization, and schooling are generally not made available to the migrant family at times, the migrants themselves refrain from obtaining the resident status in the destination states to retain their links with the place of departure or state of origin (Mohanty et al 2016). Therefore, for the purpose accounting the duration of work for interstate migrants the period up to which a migrant laborer works in the destination States by retaining his or her residency in the place of departure or the state of origin can be counted.…”
Section: IIImentioning
confidence: 99%
“…Therefore, there is an urgent need to foster migrant integration in the popular destination states of India (Sridhar et al, 2012; Mohanty et al, 2016). Interstate migrants need integration measures such as access to poverty alleviation/employment guarantee schemes (Mohanty et al, 2016).…”
Section: The Indian Contextmentioning
confidence: 99%
“…Internal migration in developing countries is a crucial livelihood strategy for low‐income households and communities and it has positive changes in both sending and receiving areas (Deshingkar and Grimm, 2005; McKenzie and Yang, 2010; Mohanty et al, 2016; Srivastava and Sutradhar, 2016; Nayyar and Kim, 2018). Despite this, internal migration continues to be viewed as a destabilising process by policy makers and they do not acknowledge the beneficial effect that it has on development (Nyberg‐Sørensen et al, 2002; Deshingkar and Grimm, 2005; Kundu and Sarangi, 2007; Geiger and Pécoud, 2013; Bhavnani and Lacina, 2015).…”
Section: Introductionmentioning
confidence: 99%